Cases without controversies uncontested adjudication in Article III courts - Pfander, James E. (Oxford University Press, 2021)
For students of the federal judiciary, the Supreme Court's encounter with the adverse-party requirement in the Defense of Marriage Act (DOMA) case, United States v. Windsor, was disappointing. The Court has rather dogmatically insisted that federal courts can hear only "definite and concrete" controversies that touch upon "the legal relations of parties having adverse legal interests." But the Court has failed to provide a coherent account of the adverse-party requirement or of how such a requirement can co-exist with a variety of clearly non-adverse or ex parte proceedings that have worked their way onto the docket of the federal courts. Since the 1790s, Congress has assigned pension claims, warrant applications, naturalization proceedings, and a surprisingly broad range of other ex parte matters to the federal courts. For example, the Foreign Intelligence Surveillance Act, a subject of recent controversy, requires the government to obtain an ex parte federal court order to conduct certain kinds of electronic surveillance. Aside from a decision nearly one hundred years ago addressing the power of the federal courts to naturalize aliens, and a few relatively uninformative decisions thereafter, the Court has failed to wrestle with the tension between adverse-party rhetoric and ex parte reality. Windsor did little to clarify matters. Doubts as to the presence of truly adverse parties had arisen early on, when the government insisted on enforcing DOMA but agreed with its nominal opponent, Edith Windsor, that the law violated her constitutional rights by denying her the beneficial federal tax treatment she would have received had she been the surviving spouse of a man instead of a woman. Yet the opinion by Justice Kennedy for a five-Justice majority announced that the disappearance of adverseness did not deprive the Court of power to reach the merits. For the majority, the adverse-party requirement was a prudential element of standing doctrine, appropriately informing the Court's discretion but not inflexibly compelling party opposition as a jurisdictional prerequisite at every stage of every case. The Court did not offer much by way of support for its conclusion that such a requirement existed or, if it did, why it was merely a matter of prudence; certainly the Court took no notice of the many instances in which the federal judiciary, without first consulting prudential considerations, proceeds in the absence of party adverseness. Justice Scalia's sharply worded dissent also added little to our understanding of the adverse-party requirement. To be sure, Justice Scalia viewed the rule as an "essential element of an Article III case or controversy," not as a prudential requirement "that we have invented." Moreover, Justice Scalia attempted to connect the adverse-party restriction to the text of Article III, placing some emphasis on the fact that the term "controversy" connotes a live dispute between opposing parties. But the Justice did not address the meaning of Article III's grant of "judicial power" or of its reference to "cases"; both terms have suggested to other readers, including Chief Justice John Marshall and Justice Joseph Story, that federal jurisdiction encompasses more than disputes between adversaries. As for history, Justice Scalia depicted Article III's case-or-controversy limits as reflecting the traditional forms of adjudication inherited from early Americans and our "English ancestors," an echo of an earlier claim that the federal judicial power extends only to the forms and actions of the English courts at Westminster. This emphasis on England and the practice of the courts at Westminster, however, not only overlooks the fact that the English Court of Chancery itself exercised jurisdiction over certain ex parte and non-adverse matters; it also tends, in its focus on the common law, to obscure the alternative forms of adjudication on which the Framers were to draw in crafting Article III. It was mainly in the equity, admiralty, and probate courts of the eighteenth century, where judges rather than juries bore primary responsibility for fact-finding, that the Framers were to encounter the range of ex parte proceedings that made their way onto federal court dockets in the early Republic. Windsor thus brought us little closer to resolving the tension between the theory and reality of the adverse-party requirement"--